Fe-MCM-22 zeolites: synthesis and study about the states of iron - Thuan, Ngo Thi; Nhu Mai, Tran Thi; Phuong Ly, Giang Thi; Tuan, Le Xuan (Vietnam Journal of Chemistry, 2014)
The Fe-MCM-22 zeolite was successfully synthesized with hexametylenimine template. Several physicochemical techniques (XRD, SEM, BET, AAS, IR and ESR) have been used to characterize this zeolite. Iron exists under three states: isolated ions in tetrahedral lattice positions, in octahedral coordination as isolated ions at cationic positions and as aggregated oxide species or hydroxide phases.Keywords: Fe-MCM-22 zeolite, synthesis, characterization, framework iron.